Aconitine induces cardiotoxicity through regulation of calcium signaling pathway in zebrafish embryos and in H9c2 cells. Issue 6 (23rd January 2020) - Li, Mengting; Xie, Xiaofang; Chen, Haimei; Xiong, Qiuyun; Tong, Rongsheng; Peng, Cheng; Peng, Fu
Abstract: Fuzi, the processed lateral roots of Aconitum carmichaelii Debx., is a traditional herbal medicine that is well known for its excellent pharmacological effects and acute toxicity. Aconitine is one of the diester‐diterpene alkaloids and well‐known for its arrhythmogenic effects. However, the effects of aconitine in zebrafish have rarely been studied. Therefore, we investigated the effects of aconitine on zebrafish embryos and H9c2 cells. Zebrafish embryos at 48 hours postfertilization were exposed to aconitine, and then, cardiac function and apoptosis were measured. Through transcriptomic analysis, the cardiotoxicity of aconitine in zebrafish embryos was involved in regulating Ca 2+ signal pathways. A reverse transcription‐polymerase chain reaction was performed to verify the expression of Ca 2+ pathway‐related genes after 12, 24, 36 and 48 hours of treatment. Meanwhile, intracellular Ca 2+ concentrations and cell apoptosis were observed in H9c2 cells treated with half‐maximal inhibitory concentration values of aconitine for 30 minutes. The protein levels of troponin T (TnT), caspase 3, Bcl‐2 and Bax were detected by western blot analysis. In vivo, 2.0 and 8.0 μm aconitine decreased the heart rate and inhibited the contraction of ventricles and atria in a dose‐ and time‐dependent manner. Furthermore, aconitine increased expression of cacna1c, RYR2, atp2a2b, Myh6, troponin C, p38, caspase 3, Bcl‐2 and Bax for 12 hours. In vitro, 1.5 and 4.5 mm aconitine caused intracellular Ca 2+ ion oscillation, increased rates of apoptosis, inhibited TnT and Bcl‐2 protein expression, and promoted caspase 3 and Bax protein expression. These data confirmed that aconitine at various concentrations induced cardiac dysfunction and apoptosis were related to the Ca 2+ signaling pathway. Abstract : Aconitine was investigated by means of a combination of experimental approaches. Data from the survival test, acridine orange test, cardiac function analysis and transcriptional analysis using zebrafish embryos as an in vivo model, as well as data from intracellular Ca 2+ ion test, apoptosis assay and western blot assay in H9c2 cells, demonstrated that cardiotoxicity of aconitine is positively related with the dose. In addition, the mechanism of dose‐toxicity relationships refers to intracellular Ca 2+ overload and apoptosis.